Radikalisme dalam Al- Qur'an: Studi Kritis terhadap Penafsiran Sayd Qutb dan Rasyid Ridlo - El-Karimah, Mia Fitriah; Mahfud, Mahfud (Al Ashriyyah, 2024)
This paper attempts to dismantle the interpretation of Qur'anic verses that are often used as radical justifications by some groups. The discourse of criticism of the interpretation of radicalism in religion has special attention to be discussed. Because in essence, religion can be interpreted as a value system that allows its adherents to be able to respect and respect other humans. This research is qualitative research with primary sources in the form of tafsir fi Dzilal al-Quran and al-Manar related to verses that are considered by some to contain interpretations of radicalism. Based on the description above, the Qur'anic verses that are claimed to have nuances of radicalism interpretation will be limited to representatives of jihad, qital and hakimiyah verses by correlating contemporary interpretations of tafsir, namely Tafsir al-Manar by Rashid Ridho (d. 1935 AD) and Dzilal al-Qur'an by Sayyid ibn Qutb (d. 1966 AD). The interpretation of jihad and war verses is considered to legitimize and base radical actions, as well as the understanding of takfiri (disbelief) which is a reference for resolving any dissent by disbelief. The results of data analysis revealed that the tafisran jihad, qital and hakimiyah in the restricted verse did not contain radical elements. The author does not find, as some have criticized, that the above verses are a reference to disbelieve everyone, fighting countries that do not apply Allah's law. Because of the limitations of the verse, it is possible that the potential for this interpretation is in other verses or in their other works.